STUDENTS’ PERCEPTION OF CITY BRANDING: THE CASE OF KASTAMONU AND KASTAMONU UNIVERSITY - Sarac, Omer; Pamukcu, Huseyin; Ulama, Sevki; Batman, Orhan (Turizam, 2019)
Recent developments in technology have led to changes in the way we manufacture as well as the amounts being manufactured allowing for more competition in the global market. Such competition is the case not only between products and businesses but also between cities, states and destinations. In this context, branding plays an important role in the marketing of cities and states. With its unique natural, historical and cultural assets, Turkey has a number of candidates for city branding. Turkish city of Kastamonu, one of the candidates for city branding, boasts many cultural assets which drive the tourism in the city. The aimed of this study was to measure the Kastamonu University, Faculty of Tourism students’ perception of city brand associated with the city of Kastamonu. A total number of 505 questionnaires were completed by the university students and the data collected was analyzed using a statistics software suite; frequencies, percentages, means, factor analysis, t-test, and one-way analysis of variance (ANOVA) were used for data processing. As a result, a total number of seven dimensions were found with respect to the students’ perception of Kastamonu as a city brand. Statistically significant differences were found between parameters such as age and gender of the students, years of academic study, income, place of origin, previous knowledge of the city, first impression of the city and current opinion about the city and these dimensions. Keywords: Marketing, Brand, Branding, City Brand, Kastamonu